Exploring the role of project work in secondary schools beyond continuous assessment - Mkimbili, Selina; Amani, Jaquiline; Hassan, Iddy; Mrema, Daudi (Papers in Education and Development, 2024)
This article presents the findings of a qualitative inquiry that explored what secondary school students in Tanzania learn from their research project work beyond just grades. Guided by Vygotsky’s (1978) constructivist theoretical perspective, the study collected data from 38 students and 10 teachers through focus group discussions and interviews, respectively. The study found that, besides obtaining grades and rewards, engaging in project work provided students with opportunities to develop research, problem-solving, creativity, communication, collaboration, and leadership skills. It further reveals that the effectiveness of project work in secondary schools is undermined by its lack of emphasis, as many schools conduct it solely as a means of continuous assessment that contributes to the student’s overall grades. However, the study documents that well-conducted research projects have the potential to cultivate and enhance important educational skills beyond the expectations of continuous assessment. The implications of the findings for policy and practice are discussed.